Metachronous Periadrenal Fatty Tissue Metastasis from Contralateral Renal Cell Carcinoma. (5th March 2013) - Alkan, Erdal; Ozkanli, Oguz; Balbay, Derya
Abstract : Contralateral adrenal metastases from renal cell carcinomas are not commonly seen. To our knowledge, we are presenting the first case of extraadrenal metastasis in the English literature, from the contralateral RCC 6 months after radical nephrectomy. Patient was treated with robotic right adrenalectomy for continuous growing of a de novo right adrenal mass of 6 × 4 × 3 cm in diameter. Tissue between vena cava, renal capsule, and inferior diaphragmatic surface was removed en block. Pathological evaluation revealed renal cell carcinoma within the fatty tissue abutting the adrenal capsule from outside with negative surgical margins. Our experience dictates that removing adrenal tissue only after identifying the adrenal borders may sometimes result in insufficient tumor removal. Therefore, adrenal containing tissue within the anatomic boundaries should be removed en block, if surgical removal is planned for metachronous tumor metastasis in the treatment of renal cell carcinoma.